Strategic Analysis And Online Marketing Plan For Mokana In The Spanish Furniture Market - Adibrata, Fahriza (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
Mokana Meubelen, a Dutch furniture company, is planning to expand into the Spanish market to capture new growth opportunities. This study explores the strategic and online marketing efforts necessary for successful market entry in Spain, focusing on Mokana’s strengths, weaknesses, and the dynamics of the Spanish furniture industry. Employing a qualitative research approach, data were collected through interviews with key stakeholders at Mokana. Internal and external analyses, including SWOT and DESTEP frameworks, were applied to evaluate the company's current position and identify opportunities and threats in the Spanish market.The findings reveal Mokana's strengths, including high-quality, customizable furniture, and a robust online presence. However, challenges such as premium pricing and limited market-specific knowledge pose obstacles to successful entry. The Spanish market presents significant potential, particularly in its growing e-commerce sector and demand for sustainable furniture. Consumer preferences in Spain, ranging from traditional to modern designs, require Mokana to adapt its product offerings and strategies to suit local tastes while leveraging its existing digital platforms.Based on the analysis, the study recommends implementing digital marketing strategies using the RACE framework, strengthening social media campaigns, and optimizing e-commerce capabilities to engage with Spanish consumers effectively. Tailoring products to align with the preferences of Spanish consumers and addressing identified challenges will position Mokana for sustainable growth. This research provides a comprehensive roadmap for Mokana’s market expansion, emphasizing the importance of strategic alignment with local market conditions and consumer behavior.